Taxon-Dependent Community Assembly of Bacteria and Protists in River Ecosystems: A Case Study from the Yujiang River - Yusen Li; Wenjian Chen; Yaoquan Han; Jianjun Lei; Bo Huang; Youjie Qin; Feng Lin; Caijin Li; Dapeng Wang; Lei Zhou (Microorganisms, 2025)
Understanding the processes that drive microbial community assembly is a fundamental question in ecology, with important implications for predicting community responses to environmental disturbances. River ecosystems are under growing pressure from human disturbances, jeopardizing their ecological functions. Here, we investigated bacterial and protistan communities along the Yujiang River using environmental DNA metabarcoding. Bacterial communities exhibited significantly greater alpha diversity and broader habitat niches compared to protists. Additionally, a negative correlation was found between alpha diversity and niche breadth for both groups. Protistan communities exhibited significantly higher beta diversity (Bray–Curtis distance) than bacterial communities, with species turnover being the principal factor driving the variations in both communities. Null model results indicated that heterogeneous selection primarily structured bacterial communities, while stochastic processes (drift) mainly governed protist communities. Redundancy analysis and Mantel tests showed significant associations between environmental factors (e.g., temperature and pH) and bacterial community composition. Moreover, the longitude of sampling sites was linked to spatial variations in both bacterial and protistan communities. Further analyses, including distance-decay patterns, variation partitioning, and multiple regression on distance matrices, demonstrated that bacterial communities were driven by both environmental and spatial factors, while protist communities exhibited a stronger response to spatial factors. These results enhance our understanding of microbial community assembly in river ecosystems and provide valuable insights for the conservation and sustainable management of freshwater systems.